State and Church Relations under Communism, National Socialism and Fascism: Some Aspects of the Problem (Forum Theologicum Sardicense, 2025)
The relationship between the State and the Church is examined through the lens of three of the most undemocratic ideologies and systems: Communism, National Socialism, and Fascism. The author’s analysis demonstrates that all three ideologies reject free will and subordinate the entire human person to the same fully natural mathematical laws and models that govern inanimate nature. This fundamental difference is the root of the incompatibilities between Communism, National Socialism, and Fascism, on one hand, and religion, on the other. The materialistic ideology of Communist, National Socialist, and Fascist states inevitably leads these regimes to attempt to completely subordinate and eventually destroy the Church. Sooner or later, this brutal coercion results in the collapse of the totalitarian state and the triumph of faith and spirit over materialism.
Keywords: Church and State Relationships; National Socialism; Communism; Modern History